Pembelajaran Sintaksis SDI Surya Buana Malang - ’Adhim, Rizka Maziyyah (Maliki Interdisciplinary Journal, 2024)
This research discusses the importance of learning the Indonesian language, particularly syntax, at the elementary school level, with a focus on SDI Surya Buana in Malang City. The Indonesian language, as a communication tool regulated by Article 36 of the 1945 Constitution, needs to be preserved amidst the influences of foreign languages and colloquial language that threaten its existence. Effective learning of syntax is key to developing strong communication skills, beginning with an understanding of sentence structure. This study employs a descriptive method to illustrate the practice of teaching syntax in the second grade at SDI Surya Buana, which implements the 2013 national curriculum, the independent curriculum, and the internal Islamic curriculum. The findings indicate that careful planning, interactive implementation, and appropriate evaluation are crucial in teaching syntax. Through an integrated thematic approach and scientific methods, students are expected to understand and construct sentences correctly, thereby maintaining the identity of the Indonesian language as part of the nation’s culture. This research emphasizes the need for greater attention to language education to safeguard the continuity and authenticity of the Indonesian language in the modern era.